Distribución de “rabia del garbanzo” en la región centro/norte de la provincia de Córdoba - Pastor, Silvina Estela; Valetti, Lucio; Scandolo, Nicolás; Perez, A.; Crociara, Clara Sonia; Paredes, Juan Andrés (Facultad de Ciencias Agropecuarias, Universidad Nacional de Córdoba, 2025)
Póster